Experience in applying the Geocomposite method on soft soils in Moscow - Chunyuk Dmitry Yuryevich; Selviyan Serafima Mikhailovna (E3S Web of Conferences, 2023)
The pace of construction of industrial and civil buildings in Russia is increasing every year. In this regard, most of the undeveloped territories are composed of weak soils, which in turn leads to an increase in construction costs and the need for additional measures. Such measures include changing physical and mechanical characteristics of soils and increasing their bearing capacity. One of the more promising methods of improving the properties of soils is the method of "Geocomposite". This method allows to form stronger artificial structural bonds between particles in the soil. When fixing soils with Geocomposite, injectors are arranged and chemical or microcement solution is supplied under pressure [4]. This method of mortar supply helps to break up weakened soil areas and fill voids. It is important to note that when consolidating soils using the Geocomposite method, it is necessary to build a test site to select the optimal pressure of solution supply and to determine the characteristics of the consolidated soil.